Congenital lobar emphysema surgical versus conservative management - Hussein, Abdulameer M.; nemat, Mohammed H.; Abood, Laith S. (Journal of the Faculty of Medicine Baghdad, 2013)
Back ground: Congenital lobar Emphysema (CLE) is a rare yet serious condition which requires early detection and management, and usually present during infancy. Patients and methods: This retrospective study aimed to review and evaluate methods adopted for the management of congenital lobar emphysema cases and it aimed to report and to document any observation which might need further research. The study retrospectively reviewed medical records of 53 cases whom were admitted to the department of thoracic surgery-medical city teaching complex over a period of 4 years (from June 2005 to June 2010). All of them had been diagnosed and managed as cases of congenital lobar emphysema based on their clinical picture and radiologic examination.Objectives: Results: The commonest age group affected were infants in the second month of life(40 patients) (75.47%), 10 patients (18.86%) within the next 3 months, 2 cases (03.77%)were over 6months old and only one case (01.88%) was over 1y. The number of male patients in this study was higher than the female patients (38 versus 15) with a male to female ratio was 2.53:1. The affected lobes were left upper lobe in 39 patients (73.60%), right middle lobe in 9 patients (16.98%), right upper lobe in 3 cases (5.66%), and right upper and middle lobes in 2 cases (3.77). Postoperative complication encountered in 6 patients; chest infection (2 patients), bronchopleural fistula and empyema (2 patients), wound infection (1 patient), and postoperative atelectasis (1 patient). Each treated accordingly. No intraoperative mortality was recorded, yet postoperative mortality happened in 3 cases, two cases due to respiratory failure and other one due to septicaemia. The significant finding in this review was that, 8 cases out of the 53, during the period of observation and conservative management, they eventually developed complete clinical improvement of their signs and symptoms and complete resolution of their radiologic findings. All other patients (45) required surgical resection, were lobectomy was the commonest type of surgical resection (39 patients), combined lobectomy and wedge resection performed in (6) patients. Conclusions: A group of cases diagnosed with CLE can benefit from a period of observation and monitoring aiming for conservative management